Partnership Implementation in Banking Industry: Parent-Subsidiary Bank Policy in Indonesia - Hartati Rahayu, Sri; Alif Febriyanto, Satrio; Angelina, Feymi (Magister of Law, Faculty of Law, University of Mataram, 2024)
Indonesia has a partnership policy as a prerequisite for foreign parties who wish to open a bank in Indonesia. This partnership policy has been known since the allowance for foreigners to own banks with a 99% stake which continues to this day in today’s era of financial industry consolidation. This paper will elaborate on the idea of implementing a partnership policy through the concept of parent-subsidiary bank between Commercial Bank with Foreign Ownership and Local Banks in Indonesia such as Regional Development Banks and People’s Economic Banks. This idea will examine the possibility, procedure, and impact of the implementation of the concept on the consolidation of the national banking industry, especially the strengthening of local banks as an effort to improve the welfare of the people as a whole. This research is normative legal research with a statutory and conceptual approach. Based on the analysis conducted in this paper, the implementation of the parent-subsidiary bank concept is in line with the positive regulations prevailing in Indonesia around strengthening the capital of Regional Development Banks and People’s Economic Banks as well as having an impact on strengthening capital and transferring technology to these local banks which have an impact on improving the services and capacity of local banks in competing in the banking industry.